Synthesis, characterization of nano-sized anatase TiO2 and its adsorption behaviour for environmental contaminant - Gupta, K.; Pandey, A.; Singh, R. P. (Cellular and Molecular Biology, 2017)
TiO2 is one of the most studied material due to its unique properties like chemical stability, non toxicity and cost effectiveness. Nano-sized TiO2 has been prepared by sol –gel method using titanium butoxide as precursor. X- ray diffraction analysis was used to characterize the phase and crystal size of the synthesized TiO2 particles. It was found that sizes of the particles ranged from 6 to 12 nanometre. FT-IR spectrum was also recorded for the TiO2 particles to detect the remaining organic residue .Heavy metals like Cr, Cu, Fe, Ni etc are considered major environmental contaminant in water due to their non biodegradable nature and adverse health effect in living beings. In this work the adsorption behavior of heavy metals towards nano-sized TiO2 was investigated.